Ռեցիդիվը՝ որպես հանցագործությունների բազմակիության տեսակ - Հայկ Մկրտչյան (ՀՀ ԳԱԱ հրատ.)
В научной статье представлен рецидив преступлений как вид множественного преступления. Исследованы мнения ученых относительно этой проблемы. Также были представлены преступления, которые совершались несовершенолетними, и в этом контексте обсуждены проблемы квалифицирования рецидива преступлений. Предложены различные решения, которые помогут улучшить внутреннее законогательство. The article focuses on the concept of recidivism as a kind of crime plurality. Opinions of international scientists on recidivism were viewed and considered. Junior crimes are also presented and in this context issues regarding the qualification of recidivism of crimes are discuss. Therefore various solutions were proposed that will help to improve the domestic legislation.
Keywords: Law